A state-level analysis of gender inequality on male and female homicide - Moore, Matthew D. (Crime & delinquency, 2021)
Inequalities have received a fair amount of study from criminologists interested in homicide and crime. The vast majority of the examinations exploring the relationship between inequality and homicide and crime have examined income inequality. Nonetheless, feminist theorists have stated that gender inequality may be predictive of all violence, not just female victimization. The UNDP gender inequality index was replicated for states in the United States and applied to overall, male, and female homicide rates. The findings demonstrate that increased gender inequality is predictive of increased overall, male, and female homicide. These findings illustrate that gender inequality is predictive of overall, male, and female homicide victimization.